2020
DOI: 10.20944/preprints202010.0342.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Youth Exposure to Hate in the Online Space: An Exploratory Analysis

Abstract: Today’s youth have almost universal access to the internet and frequently engage in social networking activities using various social media platforms and devices. This is a phenomenon that hate groups are exploiting when disseminating their propaganda. This study seeks to better understand youth exposure to hateful material in the online space by exploring predictors of such exposure including demographic characteristics (age, gender and race), academic performance, online behaviours, online disinhib… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
3
0
1
Order By: Relevance
“…; Wachs et al, 2020). Despite the increasing scientific attention to online hate speech (e.g., Döring & Mohseni, 2020; Harriman et al, 2020; Wachs et al, 2021), the current literature on offline hate speech among young people in schools is rather limited. Consequently, not much is known about determinants of adolescents’ hate speech perpetration in schools and theoretical frameworks that help to explain why adolescents engage in it.…”
mentioning
confidence: 99%
“…; Wachs et al, 2020). Despite the increasing scientific attention to online hate speech (e.g., Döring & Mohseni, 2020; Harriman et al, 2020; Wachs et al, 2021), the current literature on offline hate speech among young people in schools is rather limited. Consequently, not much is known about determinants of adolescents’ hate speech perpetration in schools and theoretical frameworks that help to explain why adolescents engage in it.…”
mentioning
confidence: 99%
“…Moreover, Reichelmann et al (2021) found that 70.7% of the 18-25-year-old respondents witnessed online hate speech in the preceding 3 months. In another study, Harriman et al (2020) found that 57% of 14-20 years-old participants reported that they had observed hate messages on social media or a website in the preceding 2 months. Regarding the European context, some studies have observed different prevalence rates of hate speech among youth and adolescents.…”
Section: Prevalence Of Hate Speechmentioning
confidence: 98%
“…This phenomenon favors the use of hate speech, characterized by the demonstration of power or expression of frustration in the face of defeat. It is a behavior that is sometimes harmful to the physical and psychological well-being, as well as the self-esteem of aggressors and victims (Breuer 2017;Harriman et al 2020;Arbeau et al 2020).…”
Section: Hate Speech In Digital Gamesmentioning
confidence: 99%